A Facile Synthesis of Two Brucine-Steroid Derivatives - Figueroa-Valverde, Lauro; Diaz-Cedillo, Francisco; Garcia-Cervera, Elodia; Lopez-Ramos, Maria; Pool-Gomez, Eduardo (Asian Journal of Chemistry, 2012)
In this study, two brucine-steroid derivative were synthesized. In first stage, the brucine-androsterone derivative was development by the reaction of N1-(2,3-dimethoxystrychnidin-10-yliden)-ethane-1,2-diamine and androsteronehemisuccinate using as catalyst a carbodiimide derivative. The second stage was achieved by the reaction of N1-(2,3-dimethoxystrychnidin-10-yliden)-ethane-1,2-diamine with b-estradiol 17-hemisuccinate to form the brucine-estradiol conjugatein presence of a carbodiimide derivative. In conclusion, in this study we show a facile procedure for synthesis of two brucine-steroid derivatives.